Domino Media To Help Know The Symbol Of Number In Children Aged 4-5 Years - Kuriah, Kuriah; Sulistianingsih, Sulistianingsih; Marliani, Lina (Worldwide Research Publishing, 2023)
The background of this research is the problem of children's ability to recognize number symbols, namely during observations it was found that Group A children of Amanah Islamic Kindergarten did not know number symbols. This study aims to describe the differences in the level of ability to recognize number symbols in Group A children of Amanah Islamic Kindergarten before and after applying domino media. This study used a quantitative approach with a pre-experimental design. The research design using one group pretest-posttest is a type of experimental research in which one group of subjects is measured at two different times. The goal is to estimate the effect of size on the variable being measured. The design of this study examines the effectiveness of the application of domino media on the ability to recognize number symbols in Group A children in Islamic Kindergarten Amanah, Losari District, Cirebon Regency. The data collected is the result of tests to recognize numbers before and after using domino media. This can be seen from the increase in the average score before and after using domino media. the symbol number has increased more significantly than before using the domino media. In conclusion, domino media can be an effective alternative to improve the ability of Group A children in Amanah Islamic Kindergarten to recognize number symbols. This study also proposes to carry out further research that integrates domino media with other number learning and considers other factors that can affect early learning abilities.